2016
DOI: 10.9799/ksfan.2016.29.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Sauce for Meat prepared with Mulberry Leaf Powder and Mulberry Fruit Powder

Abstract: Recently, the incidence of cardiovascular diseases including high blood pressure and heart disease has increased with increased meat consumption in Korea. This study was performed to determine the optimal mixing ratio among ratios of 0, 1:0, 0:1, 1:1, 2:1, and 1:2 of mulberry leaf powder to mulberry fruit powder based on the anti-inflammatory effects. Then, the quality characteristics of the sauce for meat prepared with different mixing ratios (0, 1:1, 1:2, 1:3, 1:4, and 1:5) of mulberry leaf powder to mulberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…However, in the scientific literature, there is no information about the mineral element contents of butter cookies enriched with mulberry leaf powder. Kim et al [ 30 ] evaluated the macroelement content of jelly with various levels of mulberry leaf powder (0.5, 1, 1.5, and 2%). They revealed that increasing the amount of mulberry leaf powder added significantly increased the contents of K, Ca, and Mg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the scientific literature, there is no information about the mineral element contents of butter cookies enriched with mulberry leaf powder. Kim et al [ 30 ] evaluated the macroelement content of jelly with various levels of mulberry leaf powder (0.5, 1, 1.5, and 2%). They revealed that increasing the amount of mulberry leaf powder added significantly increased the contents of K, Ca, and Mg.…”
Section: Resultsmentioning
confidence: 99%
“…Mulberry has been recognized as a functional food due to its high nutritional and phytochemical content [ 15 ] and is beneficial for human health [ 26 ]. The leaves are used as dairy animal feed, teas [ 27 , 28 ], as an additive in yogurt bites [ 29 ], jelly [ 30 ], masala biscuits [ 31 ], wheat flour cookies [ 32 ], noodles [ 33 ], and salad ingredients. Because of mulberry leaves’ medical and nutritional benefits, leaf powder may be used as a source of nutrients in food products to supplement nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the active compounds in mulberry leaves are used to treat fever and to protect the liver in Chinese diagnosis (Zhishen et al 1999) [67] . In Japan and Korea, mulberry leaves of a particular species are consumed as anti-hyperglycaemic nutraceutical foods for diabetes mellitus patients (Kim et al 2003) [29] . Dates back to almost 659 AD the utilization of mulberry leaves in the medical field was introduced by the Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…또한 생체내의 활성산소 제거 등과 같은 항산화 작용을 가져 뇌 손상 뿐 아니라 각종 만성 퇴행성 질환 예방 (Kim et al, 1999) 과 염증반응에 중요하게 관여하는 매개인자인 nitric oxide, tumor necrosis factor α (TNF-α), interleukin1β (IL1β) 및 interleukin 6 (IL6)의 생성 억제효과를 보여 항염증 (Han et al, 2005) 효과가 알려져 있어 인체에 무해한 천연색소 및 기능 성 소재로 각광받고 있다. 이러한 뽕잎과 오디의 생리활성을 활 용한 연구로는 뽕잎분말과 오디분말의 최적 혼합비율을 이용한 기능성 죽 제조 (Kim et al, 2017), 뽕잎과 오디분말을 이용한 육류용 소스 제조 및 품질평가 (Kim et al, 2016), 뽕잎두부 제 조 (Han et al, 2005), 뽕잎설기 제조 (Lee, 2016), 뽕잎당면의 생리활성 평가 (Kim et al, 2000), 뽕잎젤리 제조 (Kim et al, 2006a), 뽕잎쿠키 제조 (Lee, 2016), 뽕잎절편 제조 (Kim et al, 2000), 오디젤리 제조 (Kim et al, 2007, Moon et al, 2012 (Cho & Choi, 2007), 다른 재료 를 첨가하기에 용이하고 열량이 낮은 장점이 있다 (Choi, 2013 98 2.0 0.0 800 1) ML0MF2, mixture of mulberry leaf powder 0 g and mulberry fruit powder 2 g; ML0.5MF1.5, mixture of mulberry leaf powder 0.5 g and mulberry fruit powder 1.5 g; ML1MF1, mixture of mulberry leaf powder 1 g and mulberry fruit powder 1 g; ML1.5MF0.5, mixture of mulberry leaf powder 1.5 g and mulberry fruit powder 0.5 g; ML2MF0, mixture of mulberry leaf powder 2 g and mulberry fruit powder 0 g. 33.83±0.01 b -5.38±0.05 e 8.10 ±0.02 a 1) ML0MF2, mixture of mulberry leaf powder 0 g and mulberry fruit powder 2 g; ML0.5MF1.5, mixture of mulberry leaf powder 0.5 g and mulberry fruit powder 1.5 g; ML1MF1, mixture of mulberry leaf powder 1 g and mulberry fruit powder 1 g; ML1.5MF0.5, mixture of mulberry leaf powder 1.5 g and mulberry fruit powder 0.5 g; ML2MF0, mixture of mulberry leaf powder 2 g and mulberry fruit powder 0 g. 2) Mean±standard deviation (n=3). 3) Different superscripts within a column (a-e) indicate significant differences (p<0.05).…”
unclassified